CRAVO NORTE, CARACAS AND TLAXCALA: STAGES OF THE PEACE TALKS BETWEEN THE SIMÓN BOLÍVAR GUERRILLA COORDINATION AND THE COLOMBIAN GOVERNMENT OF CÉSAR GAVIRIA (Tzintzun, Revista de Estudios Históricos, 2022)
The article attempts to describe the development of the negotiations between the Colombian government of President César Gaviria (1990-1994) and the representatives of each of the insurgent groups that formed the Simón Bolívar Guerrilla Coordination between 1991 and 1992, a period in which a series of meetings were held in Venezuela and Mexico with hopes of seeking a negotiated solution to the armed conflict. With this, the aim is to analyze the negotiating process with all the Colombian armed organizations
Keywords: peace talks; Simón Bolívar Guerrilla Coordination; Colombian armed conflict; armed organizations; Tlaxcala